ЎЗБЕКИСТОН ҲУДУДИДАГИ ТОЖИКЛАРНИНГ ЭТНИК ТАРКИБИ (Қашқадарё воҳаси мисолида) - Турсунов, Ф.Ғ. (SCIENCE and SOCIETY, 2025)
In this article, the origin and the role of ethnic groups such as Harduri Tajiks, Khojas, Chagatai, Arghuns, Deermen, Mojars and Baluchs, belonging to the ethnic composition of the Tajiks in the Kashkadarya oasis, and in their place ethnocultural processes are highlighted.